Inhibition of parathyroid hormone secretion and parathyroid hormone-independent diminution of tubular calcium reabsorption by WR-2721, a unique hypocalcemic agent. - Hirschel-Scholz, S (1985)
Hypocalcemia has been observed in patients receiving WR-2721 [S-,2-(3-aminopropylamino)-, ethylphosphorothioic acid]. WR-2721 is a compound that, after being dephosphorylated, provides protection of normal tissues against radio- and chemotherapy. The hypocalcemic response was accompanied by a decrease in the plasma level of parathyroid hormone (PTH) and by hypomagnesemia. Our present studies in rats on the mechanism of the hypocalcemic effect of WR-2721 indicate that: (a) The phosphorylated and dephosphorylated form of WR-2721 induced an equal dose-dependent decrement in plasma calcium. (b) In intact rats a maximal hypocalcemic dose of WR-2721 reduced urinary cyclic AMP excretion from 70.5 +/- 6.3 to 38.2 +/- 3.1 pmol/ml glomerular filtration rate (GFR), a level comparable to that observed (35.9 +/- 5.2 pmol/ml GFR) in thyroparathyroidectomized (TPTX) rats. (c) WR-2721 given to TPTX rats did not significantly interfere with the calcemic effect of bovine PTH 1-34 infused at 2.5 IU/h. Likewise, the drug did not impair the PTH actions on the renal Ca and inorganic phosphate (Pi) handling, and on the urine cyclic AMP excretion. (d) In TPTX rats made normocalcemic by low Pi diet, the hypocalcemic effect of WR-2721 was only about 25% of that observed in intact animals. However, it was associated with increased urine Ca per milliliter GFR, indicating a PTH-independent inhibitory effect on tubular Ca reabsorption. (e) In WR-2721-treated intact rats, prevention of hypomagnesemia by infusing magnesium chloride did not reduce hypocalcemia. In conclusion, the hypocalcemic effect of WR-2721 is not dependent upon the presence of a phosphate group in the molecule and is not causally related to hypomagnesemia. WR-2721 appears to be a unique hypocalcemic pharmacologic agent with strong inhibitory activity on PTH secretion and additional PTH-independent action on renal Ca reabsorption.